Influence of Differ P Enrichment Frequency on Plant Growth and Plant C:N:P in a P-Limited Subtropical Lake Wetland, China - Li, Feng; Hu, Cong; Xie, Yonghong; Liu, Wenzhi; Chen, Xinsheng; Deng, Zhengmiao; Hou, Zhiyong (Frontiers in Plant Science, 2018)
Phosphorus (P) enrichment as a result of anthropogenic activities can potentially alter plant C:N:P stoichiometry. However, the influence of different P enrichment frequencies on plant C:N:P stoichiometry in P-limited ecosystems is still unclear. In this study, we conducted a P-addition experiment to elucidate the effect of various P enrichment frequencies on the plant C:N:P stoichiometry of Carex brevicuspis in a freshwater wetland at Dongting Lake, China. We used four P enrichment frequencies (treatment A: no P addition; treatment B: three 0.1 g kg−1 additions at 10-day intervals; treatment C: two 0.15 g kg−1 additions at 15-day intervals; and treatment D: one 0.3 g kg−1 addition during the experimental period) in a factorial design with an experimental duration of 30 days. Biomass accumulation was lowest in the treatment A and highest in the treatment C, and increased with decreasing P addition frequency. The shoot:root ratio did not differ significantly between the four treatments. Both foliar and root C concentrations were not significantly different between the treatments. Foliar N concentration was significantly lower in the treatment D than in the other three treatments, while root N concentration did not differ significantly between the treatments. Both foliar and root P concentrations, and foliar C:N were much higher in the treatment B than in the treatment A. However, root C:N did not differ significantly between treatments. Both foliar and root C:P and N:P of C. brevicuspis were lower in the treatment B than in the treatment A. These results indicated that different frequencies of P addition significantly influenced plant growth. Moreover, P enrichment, rather than frequency, significantly influenced plant C:N:P stoichiometry. Our results improve our understanding of the influence of different P enrichment frequencies on plant C:N:P stoichiometry and nutrient cycling in freshwater wetlands.